2007
DOI: 10.1038/sj.eye.6702979
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative complication of trabeculectomy in Ibadan, Nigeria: outcome of 1-year follow-up

Abstract: Objective To describe the post-operative complications reported in patients who had trabeculectomy with and without antimetabolite in UCH, Ibadan between 1999 and 2003 and the success rate achieved in term of the post-operative intraocular pressure (IOP). Methods A retrospective study of the records of glaucoma patients who had trabeculectomy between 1999 and 2003 and had follow-up in UCH Ibadan eye clinic for a minimum of 1 year was carried out. Results Seventy-six out of 171 eyes that had trabeculectomy duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…From previous literature, there were varying rates of short-term complications (from 2 weeks to 1 year after trabeculectomy) ranging from 5.2% to 50%. [456789] Our result is quite similar to the collaborative initial glaucoma treatment study (CIGTS)[5] which found early postoperative complications in 232 eyes (50%) during the first month after initial trabeculectomy even though most of the participants in the CIGTS were Caucasian or of African descent. Unlike our population, all the participants were never exposed to topical medications before trabeculectomy, and a limbus-based conjunctival flap technique without MMC use was used.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…From previous literature, there were varying rates of short-term complications (from 2 weeks to 1 year after trabeculectomy) ranging from 5.2% to 50%. [456789] Our result is quite similar to the collaborative initial glaucoma treatment study (CIGTS)[5] which found early postoperative complications in 232 eyes (50%) during the first month after initial trabeculectomy even though most of the participants in the CIGTS were Caucasian or of African descent. Unlike our population, all the participants were never exposed to topical medications before trabeculectomy, and a limbus-based conjunctival flap technique without MMC use was used.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of hypotony was low in CIGTS (0.9%), in which there was no use of MMC. In one study in Nigeria,[7] only one-third of the patients with glaucoma underwent trabeculectomy with intraoperative 5-FU use, and no cases of hypotony during the 1-year postoperation. This result is compatible with studies in African descent,[1516] which reported lower rates of hypotony and presumed that the thicker sclera in this population could be involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that the application of 5-FU during surgery improved IOP control, 10,23 whereas others failed to demonstrate a difference. 5,11 Whether the antimetabolite MMC controls IOP better than 5-FU is unclear. 24,25 A retrospective study from West Africa, comparing MMC and 5-FU over a long follow-up time found the use of intraoperative MMC to be associated with a lower likelihood of requiring postoperative medications and a greater likelihood of achieving IOP-lowering (IOP < 21 mm Hg) without medications relative to the use of 5-FU.…”
Section: The Role Of Antimetabolitesmentioning
confidence: 99%
“…[4][5][6][7][8] There are conflicting results regarding the effect of antimetabolites on IOP control in African populations. 5,[9][10][11] Clinical trials that compared trabeculectomy with and without MMC have indicated a beneficial effect of the agent on IOP reduction among black people, 6,12,13 but most studies rarely extend beyond a follow-up of 2 years 4,14-16 and suffer from heavy loss to follow-up. 5,10,14 A greater risk of thin, leaking blebs, hypotony with vision decrease, and late endophthalmitis have been reported with the use of MMC during trabeculectomy.…”
mentioning
confidence: 98%